Aurora-A/FOXO3A/SKP2 axis promotes tumor progression in clear cell renal cell carcinoma and dual-targeting Aurora-A/SKP2 shows synthetic lethality - Pu Li; Tingting Chen; Peng Kuang; Fujun Liu; Zhongmin Li; Fangfang Liu; Yu Wang; Wenfeng Zhang; Xiuyu Cai (Cell Death and Disease, 2022)
Abstract Renal cell carcinoma (RCC) is a common malignant tumor in the world. Histologically, most of RCC is classified as clear cell renal cell carcinoma (ccRCC), which is the most prevalent subtype. The overall survival of patients with ccRCC is poor, thus it is urgent to further explore its mechanism and target. S-phase kinase-associated protein 2 (SKP2) is overexpressed in a variety of human cancers and is associated with poor prognosis by enhancing tumor progression. However, it is unclear whether or how SKP2 is involved in ccRCC progression. Here, we reported that overexpression of SKP2 enhanced cell proliferation of ccRCC, while SKP2 depletion exhibited the opposite effect. Bioinformatic analyses found that SKP2 was positively correlated with Aurora-A (Aur-A) in ccRCC. The protein and mRNA levels of SKP2 were elevated or reduced by Aur-A overexpression or silencing, respectively. It was further found that Aur-A caused an increase phosphorylation of FOXO3A, which is a negatively transcription factor for SKP2. Interestingly, SKP2 mediated ubiquitylation and degradation of FOXO3A depend on the kinase activity of Aur-A. The combination of Aur-A inhibitor MLN8237 and SKP2 inhibitor SZL P1-41 showed a synergistic tumor growth inhibition in vivo and in vitro of ccRCC models. Thus, our data reveal that Aurora-A/FOXO3A/SKP2 axis promotes tumor progression in ccRCC, and the double inhibition of SKP2 and Aur-A shows significant synergistic effect, which indicates a potential new therapeutic strategy for ccRCC.